Thermal Control Design and Analysis of the Optical Telescope of an Earth Observing Satellite - Hussain, Jahanzaib (Department of Electrical Engineering, 2023)
In an optical telescope on an Earth observing satellite, the thermal stability is of vital importance to ensure optimal performance. During orbital operation in space, the nonsymmetrical distribution of temperature and high temperature variations on the telescope structure result in thermal deformation, which ultimately degrades the optical performance of the telescope. Typically, the main aim of thermal control design is to ensure that the telescope stays within a certain temperature range for optimum performance. The purpose of this thesis is to design the thermal control system of a high-resolution telescope and simulate its transient and steady state thermal behavior along with its imaging sensors using a thermal mathematical model to improve the performance of the telescope by conducting thermal analyses. Mainly in-operational conditions during orbit are considered in this thesis because the telescope only operates when the satellite becomes stable after launch. A detailed thermal model of the telescope is developed using the FEMAP TMG 11.4 software for analysis and optimization of thermal control design. With this model, different hot and cold, operational and non-operational thermal cases are analyzed. Furthermore, this dissertation also gives details of the assumptions taken at certain points of the analyses.